Penggunaan Media Plastisin pada Kemampuan Motorik Halus Anak Usia Dini di RA Yaa Bunayya - Nova Nur Hizzah; Syamsiah Depalina; Annisa Wahyuni (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
The research aims to answer how the use of plasticine media affects the fine motor skills of young children at RA Yaa Bunayya, Mompang Julu Village. This type of research is descriptive research with a qualitative approach. The data collection process takes the form of observation, interviews and documentation. The results of the research are the fine motor skills of young children in RA Yaa Bunayya Mompang Julu Village, showing that the use of plasticine media in children has been proven to provide a useful approach in various aspects of development. Through plasticine media activities, children at RA Yaa Bunayya develop various aspects of their fine motor skills in a fun and creative way. The use of plasticine media provides a stimulus that can improve children's fine motor skills, such as involving fine movements of forming, pinching and rolling plasticine. Using plasticine media in children can also develop children's creativity. As for the convenience and difficulty, namely the ease of using plasticine media for children, namely that it can develop fine motor skills and attract children's attention, because plasticine media can be shaped by children with a soft texture and can train coordination in children's hands, and the difficulty is that children do not focus on using plasticine media, difficulty in grasping, namely that young children do not have enough grip strength to form plasticine.